Modifikasi Heat Moisture Treatment (HMT) Pati Sagu dengan Variasi Kadar Air dan Aplikasinya pada Brownies Kukus: The Modification of Heat Moisture Treatment on Sago Starch with Varying Moisture Contents and Application in Steamed Brownies - Maysa, Hana; Shanti Fitriani; Ayu, Dewi Fortuna (Universitas Djuanda, 2026)
Sago starch is a local gluten-free carbohydrate source with potential as a wheat flour substitute. However its utilization in steamed brownies is still limited due to its firm texture caused by high amylose content. This limitation can be addressed through physical modification using heat moisture treatment (HMT), which reduces amylose content and improves starch functional properties. The study was conducted using a completely randomized design with four treatments (native starch, HMT 27%, 30%, and 33%) and four replications. Data were analyzed by ANOVA, Duncan’s Multiple Range Test (DMRT) at the 5% level, and paired sample t-test for sensory evaluation. The results showed that HMT moisture levels significantly affected water absorption capacity, swelling power, solubility, amylose content, and moisture content. The selected treatment was HMT 27% (P2), with a water absorption capacity of 0.91 g/g, swelling power of 10.78 g/g, solubility of 23.64 g/g, amylose content of 26.60%, and moisture content of 11.43%. Sensory evaluation confirmed that steamed brownies prepared with HMT 27% starch were more preferred than those made with native starch.